Bajo Fishing Tradition: Implications and Conformity with UNCLOS in the Context of Protecting Traditional Fishermen's Rights - Hengki, Hengki; Criemen Lokovettor, Agrifin Bernadeth; Anwar, Rian Nugraha (IHSA Institute, 2024)
This research explores the dynamics of interaction between the traditional fishing practices of the Bajo tribe in Indonesia and international regulations covered by the 1982 United Nations Convention on the Law of the Sea (UNCLOS). The Bajo tribe, known for their maritime life and sustainable approach to fishing, facing new challenges in the era of globalization and environmental change. Although UNCLOS aims to regulate the use of the sea and its natural resources globally, the absence of a clear definition of traditional fishing rights causes uncertainty in Bajo practices. This research uses normative juridical methods to examine how the Bajo tribe adapts to UNCLOS provisions while maintaining their fishing traditions. The research results show that the Bajo tribe has attempted to adopt new practices such as mariculture to overcome restrictions posed by modern regulations. However, the shift away from traditional methods sometimes leads to environmentally damaging practices. This study suggests the need for a more inclusive legal framework that integrates local wisdom in international regulations, to recognize and protect the traditional rights of the Bajo tribe, thereby enabling them to maintain their way of life without threatening the marine ecosystem. This research provides insight for policy makers and stakeholders in navigating between cultural preservation and environmental sustainability in a global context